Cutaneous Myiasis Caused by Chrysomya megacephala in an Infant with Psoriasis Vulgaris - Siripan Sangmala; Kumpol Aiempanakit; Puttichart Khantee; Theerakamol Pengsakul (Karger Publishers, 2020)
Cutaneous myiasis is an infestation of the skin by fly larvae, which usually occurs in adults. We present a case of cutaneous myiasis caused by Chrysomya megacephalain a 3-month-old infant with psoriasis vulgaris. In this case report, we highlight the clinical, histopathologic, taxonomic identification, and treatment of cutaneous myiasis occurring in psoriatic skin.